Широкополосные трансформаторы для интегральных схем в технологии LTCC - Glubokov, A. A.; Bondar, D. B.; Shelkovnikov, B. N. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
Designs of monolithic transformers developed for implementation in LTCC technology (DuPont System 951) are presented. A new design of a broadband integrated balun is proposed, which allows for a reduction in device size. The topologies and characteristics of the transformers are described, and the dependence of their parameters on the main geometric dimensions is analyzed. The operation of a ring double-balanced mixer using the developed transformers is demonstrated.